The Presence of Nuclear Cactus in the Early Drosophila Embryo May Extend the Dynamic Range of the Dorsal Gradient - O’Connell, Michael D.; Reeves, Gregory T. (PLOS Computational Biology, 2015)
Author Summary In the early stages of development, an embryo must establish the beginnings of a body plan in order to grow organs and limbs in the right places. Across the fruit fly embryo, proteins known as morphogens cause chain reactions that eventually lead to the growth of many different body parts. One specific morphogen, known as Dorsal, is distributed in a gradient across the dorsal-ventral (DV) axis of the embryo. The Dorsal gradient has recently been measured in live embryos using a fluorescently-tagged version of Dorsal, but the gradient measured by fluorescence microscopy seems to be too narrow to pattern all of the DV axis. Using a mathematical model of the Drosophila embryo, we have proposed a solution to this outstanding problem: namely that Cactus, the inhibitor to Dorsal, is present with Dorsal in nuclei across the embryo, which creates a disparity between the gradient measured by fluorescence and the gradient measured by gene expression. By using distinct model equations for active and inactive pools of Dorsal, we were able to recreate the dynamics of the Dorsal gradient and the expression patterns of its target genes with a high level of accuracy, showing that mathematical models may be critical for properly interpreting fluorescence data.